Cell surface concentrations and concentration ranges for testing in vitro autocrine loops and small molecules. - Nikhil Mittal (PLoS ONE, 2012)
A common assumption made when performing in vitro cellular assays is that the concentration of substances in the culture system is uniform. However, since the cells that internalize and secrete substances reside at the bottom of the well, it is conceivable that a concentration gradient could arise across the fluid layer. Importantly, the concentration of a substance in the vicinity of a cell, which is the concentration of interest, cannot be measured via existing methods. In this work a simple strategy for estimating the concentration of a chemical species at the surface of a cell is presented. Finally, this result is used to outline a method for determining the appropriate concentration ranges for testing in vitro autocrine loops and small molecules.